The Need and Possibility of Bilingual Teaching of Computer Science in Universities of the Republic of Tuva - Dolana O. Kuular (Открытое образование (Москва))
The purpose of the study. In educational institutions of the national regions of the country, bilingual education can acquire an important meaning in ensuring the quality of the educational process. Bilingual subject learning and mastering of subject knowledge by students in a certain area based on the interconnected use of two languages (native and state) is of not only educational interest. In this regard, the purpose of the paper is to study the bilingual portrait of residents of the Republic of Tuva, identify the need for bilingual teaching of students in computer science and the feasibility of including bilingual means and methods of teaching in their training, using the example of Tuva State University.Materials and methods. To achieve the set goal, the following methods were used: the mental approach of N. Pak to substantiate the need for bilingual education of students living in national regions; the competence approach in designing and processing questionnaire questions; the inversion approach of D. Barkhatova in developing tools and methods for bilingual education in computer science. A set of complementary research methods was also used: theoretical (analysis of sources on the research problem, specification of data, generalization of psychological and pedagogical literature, comparison of data, deduction, substantive interpretation, analysis of results) and empirical (questionnaires, testing, processing and analysis of the obtained results).Results. The definition of the bilingual portrait of the residents of the Tuva Republic, as well as the identification of the need for bilingual teaching of computer science to students of the Tuva State University was carried out using specially developed questionnaires. The analysis of the questionnaire data showed that the number of bilinguals in the Republic of Tuva is 82%, among the students of the Physics and Mathematics faculty of the University – 99%. The number of surveyed lecturers, students and parents who consider bilingual education in the Republic of Tuva important exceeds 70%. Thus, the development of bilingual education in the study of subjects at school and university is becoming not only possible, but also necessary. To determine the scientific and methodological directions for the development of bilingual teaching of computer science at school and university, samples of different options for presenting educational information in bilingual textbooks on the topic “Information theory” were developed. An expert survey and a questionnaire among students revealed the fact of preference for textbooks with a synchronous presentation of content in two languages.Conclusion. The statistical data of the questionnaire survey allowed us to present a bilingual portrait of the residents of the Republic of Tuva in general, and the students of Tuva State University in particular. It should be noted that for a significant majority of students, Tuvan is their native language, and Russian is the language of study. The analysis of the questionnaire data shows the relevance and necessity of bilingual teaching of subjects at school and university. This position was expressed by a significant part of the respondents, including lecturers, parents and students. The results of the study allowed us to determine the most preferable format for presenting the content of educational bilingual resources in synchronous and “inverted” form. It is certainly necessary to develop research of the mechanisms of bilingual thinking and, on their basis, create methodological systems for bilingual teaching of subjects in schools and universities of the Republic of Tuva.